Pipe-Routing and Pathfinding in 3D (Student Abstract) - Nobes, Thomas K. (Proceedings of the International Symposium on Combinatorial Search, 2023)
Pipe-routing in 3D is a common problem in the design of industrial plant layouts. Here, we aim to minimise the structural cost of the plant (which can have multi-billion dollar budgets), while maintaining safety and engineering constraints. We tackle this problem by developing efficient methods for optimal 3D search. We contribute an adaption of Jump Point Search, a well-known symmetry-breaking technique for 2D grids, into 3D: in contrast to related work, our algorithm preserves path feasibility. In combination with a novel method for limiting over-scanning, we report search time speedups of up to an order of magnitude on benchmarks in the literature. We further develop three new and varied voxel benchmark data sets sourced from 3D applications in the literature in order to provide better opportunities for differentiating competing techniques. Towards pipe-routing, this work also identifies several remaining issues for translating the size of industrial domains and their associated constraints into 3D search.